Chemical bonds deviation in NH₃, PH₃, AsH₃, and SbH₃ molecules - Okhrimenko, B.A.; Gaididei, G.I.; Samoilenko, D.M. (Functional Materials, 2004)
Force matrices for PH3, ASH3 and SbH molecules have been computed. Approximation for two anharmonic parameters separately for stretching and bending vibrations is used. Form parameters for the investigated molecules are obtained. X-H bond deviation angles are calculated to be 3.9°, 5.3°, and 5.4°, respectively. Negative values for anharmonic parameters are obtained in some cases. This may be caused by deflection of potential energy curve from parabola toward the dependence of higher degree. Рассчитаны силовые матрицы молекул РН3, ASH3, ЭЬНз. Использована аппроксимация с двумя параметрами ангармонизма, отдельно для валентных и деформационных колебаний. Для исследованных молекул получены параметры форм колебаний. Углы девиации X-H связей равны соответственно 3,9°, 5,3°, 5,4°. В некоторых случаях получены отрицательные значения для ангармонических параметров, что может быть обусловлено отклонением зависимости потенциальной энергии от параболической в сторону более высокой степенной зависимости. Розраховано силові матриці молекул PH3, ASH3, SbH3. Використано апроксимацію з двома параметрами ангармонізму, окремо для валентних і деформаційних коливань. Для досліджених молекул отримано параметри форм коливань. Кути девіації X—H зв’язків дорівнюють відповідно 3,9°, 5,3°, 5,4°. У деяких випадках отримано від’ємні значення для ангармонічних параметрів, що може бути обумовлено відхиленням залежності потенціальної енергії від параболічної у бік більш високої степеневої залежності.